Cell-Free SHOX2 DNA Methylation in Blood as a Molecular Staging Parameter for Risk Stratification in Renal Cell Carcinoma Patients: A Prospective Observational Cohort Study. (1st April 2019) - Jung, Maria; Ellinger, Jörg; Gevensleben, Heidrun; Syring, Isabella; Lüders, Christine; de Vos, Luka; Pützer, Svenja; Bootz, Friedrich; Landsberg, Jennifer; Kristiansen, Glen; Dietrich, Dimo
Abstract: BACKGROUND: Novel targeted treatments and immunotherapies have substantially changed therapeutic options for advanced and metastatic renal cell carcinomas (RCCs). However, accurate diagnostic tests for the identification of high-risk patients are urgently needed. Here, we analyzed SHOX2 mRNA expression in RCC tissues and SHOX2 gene body methylation quantitatively in circulating cell-free DNA (ccfDNA) and RCC tissues with regard to risk stratification. METHODS: The clinical performance of SHOX2 methylation was tested retrospectively and prospectively in a training and testing cohort of RCC tissue samples (n = 760 in total). SHOX2 mRNA expression analysis was included in the training cohort. In matched blood plasma samples from the testing cohort (n = 100), we prospectively examined the capability of pretherapeutic quantitative SHOX2 ccfDNA methylation to assess disease stage and identify patients at high risk of death. RESULTS: SHOX2 gene body methylation was positively correlated with mRNA expression in RCC tissues (training cohort: Spearman ρ = 0.23, P < 0.001). SHOX2 methylation in tissue and plasma strongly correlated with an advanced disease stage (training cohort: ρ = 0.28, P < 0.001; testing cohort/tissue: ρ = 0.40, P < 0.001; testing cohort/plasma: ρ = 0.34, P = 0.001) and risk of death after initial partial or radical nephrectomy [training cohort: hazard ratio (HR) = 1.40 (95% CI, 1.24–1.57), P < 0.001; testing cohort/tissue: HR = 1.16 (95% CI, 1.07–1.27), P = 0.001; testing cohort/plasma: HR = 1.50 (95% CI, 1.29–1.74), P < 0.001]. CONCLUSIONS: Pretherapeutic SHOX2 ccfDNA methylation testing allows for the identification of RCC patients at high risk of death after nephrectomy. These patients might benefit from an adjuvant treatment or early initiation of a palliative treatment.